2014
DOI: 10.1352/1944-7558-119.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Epilepsy in Older Adults With an Intellectual Disability in Ireland: Associations and Service Implications

Abstract: There are limited studies on the prevalence of epilepsy and co-morbid conditions in older adults with an ID. To begin to address this prevalence of epilepsy was estimated for participants in the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing. Associations with demographic variables and co morbid health conditions were examined. It was found that prevalence was high (30.7%); but declined as people aged. Those with epilepsy were less likely to live with family, independently or in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 25 publications
0
34
2
Order By: Relevance
“…Although it is accepted that the prevalence increases with the severity of disability (Lhatoo & Sander, 2001;McGrother et al, 2006), we found no difference between patients with severe and profound ID in our sample, and both are lower than the prevalence reported by McCarron et al (2014) who found a prevalence of 60.3% in the severe and profound population living in residences. It should be noted that our sample is composed exclusively of women, as some studies found a higher prevalence in this group (McCarron et al, 2014) while others did not (McGrother et al, 2006).…”
Section: Discussioncontrasting
confidence: 97%
“…Although it is accepted that the prevalence increases with the severity of disability (Lhatoo & Sander, 2001;McGrother et al, 2006), we found no difference between patients with severe and profound ID in our sample, and both are lower than the prevalence reported by McCarron et al (2014) who found a prevalence of 60.3% in the severe and profound population living in residences. It should be noted that our sample is composed exclusively of women, as some studies found a higher prevalence in this group (McCarron et al, 2014) while others did not (McGrother et al, 2006).…”
Section: Discussioncontrasting
confidence: 97%
“…Patterns of neurological disease were also different. Epilepsy was the predominant neurological condition in IDS-TILDA (36%) [33], levels of epilepsy are higher in people with ID compared to those in the general population [65]. Other DBI studies most commonly reported dementia or cognitive impairment [24,26,27,46,48,53,60,66] both of which are difficult to assess in people with ID (Table S6).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…As highlighted by Bigby (), the term ‘older people with ID’ encompasses a diverse group of people “across a broad age range, diverse life experiences, abilities and diverse background” (Strnadová & Evans, , p.13). For the purpose of this article, the term “older adults” is used for a group of people who are 40 years and older (see also Burke, McCarron, Carroll, McGlinchey, & McCallion, ; McCarron, O'Dwyer, Burke, McGlinchey, & McCallion, ; Strnadová & Evans, ), who have diverse life experiences and backgrounds. The decision to focus on people aged 40 years and older allowed the capture of a broader picture showing the experiences of people with ID, as well engaging a larger group of participants.…”
Section: Introductionmentioning
confidence: 99%